Pengelolaan Coorporate Social Responsibility Menurut Peraturan Perundang-undangan di Indonesia - Lili Naili Hidayah; Raffles Raffles; Pahlefi Pahlefi (Universitas Batanghari Jambi, 2020)
Corporate Social Responsibility (CSR) is one of the obligations that must be carried out by companies in accordance with the contents of article 74 of Law Number 40 of 2007 concerning Perseroan Terbatas. The purpose of this study is to find out about the ideal management of CSR for limited liability companies. This research is a normative study, using a conceptual approach and legislative approach. Based on the results of the study found that the CSR obligation norms for the company seem indecisive, because Social Responsibility has not been explicitly set about CSR mechanisms specifically in regulations, standards